Missale notatum Lundense pars aestivalis: results of previous research of the source and facsimiles - Adamko, Rastislav (Peter Lang, 2022)
The structure of the source / Rastislav Adamko -- Historical context. The beginnings and the development of Christianity in the province of Scania up to the fifteenth century / Zuzana Zahradníková ; The peregrination of the missal / Rastislav Luz -- A few preliminary notes from a codicological and liturgical perspective / Adam Sýkora. Binding ; Internal contents of the codex ; Folio layout ; Lacunae ; Liturgical notes ; Ordinarium ; Proprium de tempore ; Communae sanctorum ; Comparison of two commune -- The liturgical and musical features of the missal. Calendar / Rastislav Adamko ; The notation of the codex / Eva Veselovská ; Alleluia chants / Rastislav Adamko ; The offertories / Eva Veselovská ; Some textual and musical/modal elements of selected chants / Janka Bednáriková ; Votive masses / Rastislav Adamko, Zuzana Zahradníková, Janka Bednáriková.